Long-term outcomes of additional surgery versus surveillance-only clinical decision for early colorectal cancer patients after non-curative endoscopic resection: a meta-analysis - Chun-Zeng Jia (BMC Gastroenterology)
Abstract Objectives The clinical decision-making regarding post hoc management of early colorectal cancer (CRC) patients who have undergone non-curative endoscopic resection (ER) remains a subject of debate. This systematic review and meta-analysis aims to compare the clinical outcomes between patients undergoing additional surgery and those receiving surveillance only. Methods A comprehensive literature search was conducted across three major medical databases: PubMed, Embase, and the Cochrane Library. STATA software was utilized for pooling analysis. The methodological quality of the included studies was assessed using the Newcastle–Ottawa Quality Scale. Results A total of 15 eligible studies encompassing 3,508 early CRC patients were included in this meta-analysis (additional surgery group: 1,974 cases; surveillance-only group: 1,533 cases). All included studies demonstrated good methodological quality, with Newcastle–Ottawa scores no less than 6. The results of the meta-analysis indicated that compared to the surveillance-only group, patients in the additional surgery group exhibited significantly improved overall survival (OR = 2.95, 95% CI: 2.05–4.24, P < 0.05), enhanced recurrence-free survival (OR = 2.53, 95% CI = 1.38–4.62, P < 0.05), a reduced recurrence rate (OR = 1.96, 95% CI = 1.22–3.13, P < 0.05), and a lower local recurrence rate (OR = 2.35, 95% CI = 1.12–4.95, P < 0.05). No significant sources of heterogeneity were identified among the studies analyzed; publication bias was also deemed acceptable across these investigations. Furthermore, we performed subgroup analyses based on inclusion criteria and age stratification which revealed notable differences in effect sizes between groups (JSCCR subgroup: OR = 2.09; 95% CI = 1.32–3.30 versus Non-JSCCR subgroup: OR = 1 .54; 95% CI = 0.89 -2.65, indicating negative results). Pooling analysis showed no significant difference between subgroups when stratified by age using a cutoff value of 65 years old. Conclusions Compared to patients who underwent surveillance only, those receiving additional surgical treatment demonstrated superior outcomes in terms of overall survival, recurrence-free survival, recurrence rates, and control of local recurrences. This suggests that such an approach may represent a more optimal clinical decision for early-stage colorectal cancer (CRC) patients who have received non-curative endoscopic resection (ER). Furthermore, this study indicates that the inclusion criteria significantly influence the reported outcomes. Notably, age did not affect the recurrence rate. Overall, this is the first meta-analysis aimed at exploring and clarifying this ongoing controversy.